Forecast of the Volume of Expenses for the Payment of Old-Age Insurance Pensions in the Russian Federation until 2035 - V. F. Sharov; I. V. Balynin; M. L. Sedova (Финансы: теория и практика, 2024)
The article is devoted to the assessment of the impact of demographic processes on the volume of expenses for the payment of old-age insurance pensions in the Russian Federation. The purpose of the study is to make a forecast of the volume of expenses of the Russian Social Fund budget for the payment of insurance old-age pensions for the period up to 2035, taking into account population fluctuations in 3 scenarios: optimistic, probable and pessimistic. The relevance of study is due is due to the influence of demographic processes on the pension system of the Russian Federation. The results obtained are new, they can be used in the practical activities of the state authorities of the Russian Federation, in the conduct of scientific research and in the educational process, etc. The authors used a multifactorial dynamic model in the form of a system of stochastic differential equations with parameters, and numerical calculations were carried out on a discrete approximation of this model. The authors revealed that with a pessimistic version of the population forecast, the volume of budget expenses of the Pension and Social Insurance Fund of the Russian Federation for the payment of insurance pensions (excluding early appointment) for 2023–2035 will increase by 56.67% (which in monetary terms is 4.22 trillion rub.); with a probable one — by 60.39% (which in monetary terms is 4.50 trillion rub.); with a pessimistic one — by 66.02% (which in monetary terms is 4.93 trillion rub.). It is important to note that any of the forecast, due to the population decline in the forecast period, assumes an increase in the volume of expenses for the payment of insurance pensions at rates below inflation (the latter, according to the minimum estimates of the authors of the article, will amount to 74.76%).